ENVIRONMENTAL AND ENERGY UTILIZATION OF MUNICIPLE WASTE – ONE PRODUCT, TWO SOLUTIONS (ETIMA, 2024)
The world is facing an increasing need for energy which leads toward escalated exploitation of natural resources, mostly fossil fuels resulting with environmental pollution and global warming. Hence, the problem of finding and using alternative and clean energy sources is self-imposed. The environmental pollution problem increased the interest in allocating more funds for scientific and research work on the use of biodegradable waste, thus in many countries increased number of new power plants which utilize biomass and/or biogas increased. Biogas is an interesting and important source of energy, especially when is generated from organic waste with an anaerobic digestion procedure. By digesting biodegradable waste originating from various organic sources such as mowing grass, cutting branches, biomass waste from farms and agricultural by-products, etc., in anaerobic conditions, the waste is fermented, and biogas is obtained as an energy source. Simultaneously, parasites and pathogenic bacteria are significantly reduced by more than 90%, which protects the groundwater, the disposal of waste in landfills, which causes water and land pollution, is reduced, and quality fertilizer is obtained for agriculture and other needs.North Macedonia as primary agricultural country has large quantities of this type of waste which is a good prerequisite for their rational economical use to obtain both, electricity and heat. Production and utilization of biogas additionally opens opportunities for establishing a free market of electricity produced from renewable energy sources. Finally, produced biogas could find its utilization value as renewable energy source for various final customers starting from the largest, up to individual households or business users, as well as for utility companies for gasification of cities or gas stations.
Keywords: energy; Biomass; renewable